Orbital Meningoencephalocele Due to Extraventricular Neurocytoma: Case Report - Andrea Cattalani; Vincenzo Grasso; Matteo Vitali; Gian Paolo Longo; Narciso Mariani; Andrea Barbanera (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2016)
Extraventricular Neurocytoma (EVN) is a rare primary tumor of Central Nervous System (CNS). To date, no cases have been reported in International Literature, about EVN associated to meningoencephalocele as manifestation of subacute increased intracranial pressure. We report the first case of EVN that manifested with diplopia and ocular motor disorders due to intraorbital meningoencephalocele through a bone gap in the orbital roof. Diagnosis of EVN is challenging and its differential diagnosis with more aggressive lesions is mandatory. Complete surgical removal does not need any adiuvant therapies and permits to control tumor growth and symptoms related to intracranial pressure.